Intraoperative Radiographic Technique for Visualization of Bicortical or Tricortical Anteromedial Sacral Screw Placement. Issue 3 (April 2018) - Jain, Nikhil; Yu, Elizabeth
Abstract : The bicortical anteromedial sacral screw trajectory is the most widely used for S1 screw fixation. The assessment of anterior cortex purchase is difficult on a lateral view due to the overlapping bony anatomy of the sacrum and pelvis. We describe the intraoperative radiographic technique for a personalized pelvic inlet view that is perpendicular to the superior sacral surface to visualize sacral screw placement. This technique allows for assessment of anterior cortex purchase with anteromedial angulation in the same view. Abstract : Supplemental Digital Content is available in the text.